Decoding the Implementation of ICT Interventions in Agriculture: A Study Among Officials from Selected Developing Nation - Joshi, Divyata; Shilpa, B; Gopichand, Balusu; Shirur, Mahantesh (Journal of Agricultural Extension Management, 2024)
The information communication technologies are playing major role in transforming the way the agricultural extension services are delivered across the globe. However, extension systems in many developing nations are yet to witness the impact of ICTs in the field of agricultural extension delivery due to the slow pace of ICT adoption in these countries. This paper presents a case of Government of India initiative to facilitate the dissemination of ICT interventions as means of agricultural extension advisory delivery through field extension functionaries in developing countries. The paper presents thedetails of the types of Back at Work Plans identified by the respondents post-training and associated strategies and constraints in implementing the back at work plans of ICT interventions as part of their job role. The broad themes on which the respondents identified their problems were; data management in extension services, post-harvest management or market led extension, production system management and resource management in crop production/protection. Mobile based application was the highest preferred solution by the respondents to address the problems of agriculture extension delivery system. Coordination among stakeholders and budgetary support are identified as major constraints for integrating the ICT interventions in the extension service delivery.